Information channel diagrams: an approach for modelling information flows - Durugbo, Christopher; Hutabarat, Windo; Tiwari, Ashutosh; Alcock, Jeffrey R. (Springer Science Business Media, 2012)
In this article, the ‘information channel diagram' (ICD) approach is introduced as a diagrammatical tool for modelling information flow during the delivery phase of organisations in which goods are deployed or delivered to customers. An initial review and evaluation of current tools for modelling information flow will be conducted based on the characteristics of information flow during the delivery phases in organisations. Diagrammatic primitives and a prescribed modelling methodology for developing an ICD will be presented, and a case scenario of the delivery phase of an organisation within the health care sector will be applied to demonstrate the use of the ICD. The article concludes by discussing some applications, generalisation potential and limitations of the ICD approac